Effectiveness of Official Counseling Practices To Understanding Efforts Of The First 1000 Days Of Life Prospective Brides In The Working Area Of Religious Affairs Office, Bengkulu City: Qualitative Study: Efektifitas Praktek Konseling Petugas Terhadap Upaya Pemahaman 1000 Hari Pertama Kehidupan Calon Pengantin di Wilayah Kerja Kantor Urusan Agama Kota Bengkulu: Studi Kualitatif - Anang Wahyudi; Mujayanto (Media Gizi Indonesia, 2023)
Reducing the prevalence of stunting in children needs to involve cross-sectors, one of which is the KUA (Office of Religious Affairs) which has officers who give lectures related to religion. The model for health counselors, especially nutrition, is the empowerment of religious officers in the Office of Religious Affairs who will provide materials to the prospective bride and groom, after the religious officers of the prospective bride and groom receive provision of knowledge on nutritional health, which in this case is the first 1000 days of life to prevent stunting. The purpose of the KUA health counselor is to change the behavior of the prospective bride and groom towards healthy behavior. The working mechanism of this health counselor model is (1) the religious officers of the prospective bride and groom receive health knowledge, especially nutrition, provided by members of the community service, (2) these counselor officers convey their knowledge to the prospective bride and groom in the form of messages accompanied by service members public. The purpose of this study is to analyze the effectiveness of Officer Counseling practices on Understanding Efforts of 1000 HPK Candidate Brides in the Work Area of the Office of Religious Affairs in the City of Bengkulu and how the factors influence it. Qualitative descriptive research method with a focus group discussion approach.